The relationship between the pan-immune-inflammation value and long-term prognoses in patients with hypertension: National Health and Nutrition Examination Study, 1999–2018 - Wu, Bo; Zhang, Chenlu; Lin, Shuqiong; Zhang, Yanbin; Ding, Shan; Song, Wei (Frontiers in Cardiovascular Medicine, 2023)
Abstract: Background: Direct antihypertensive therapy in hypertensive patients with a high CVD risk can reduce the incidence of cardiovascular death but increase adverse cardiovascular events, so additional ways to identify hypertensive patients at high risk may be needed. Studies have shown that immunity and inflammation affect the prognoses of patients with hypertension and that the pan-immune-inflammation value (PIV) is an index to assess immunity and inflammation, but few studies have applied the PIV index to patients with hypertension. Objective: To explore the relationship between the PIV and long-term all-cause and cardiovascular mortality in patients with hypertension. Method: Data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 with a mortality follow-up through December 31, 2019, were analyzed. A total of 26,781 participants were evaluated. The patients were grouped based on PIV levels as follows: T1 group (n=8,938), T2 group (n=8,893), and T3 group (n=8,950). The relationship between the PIV and long-term all-cause and cardiovascular death was assessed by survival curves and Cox regression analysis based on the NHANES recommended weights. Result: The PIV was significantly associated with long-term all-cause and cardiovascular mortality in patients with hypertension. After full adjustment, patients with higher PIV have a higher risk of all-cause [Group 3: HR: 1.37, 95% CI: 1.20-1.55, P<0.001] and cardiovascular [Group 3: HR: 1.62, 95% CI: 1.22-2.15, P<0.001] mortality. Conclusion: Elevated PIV was associated with increased all-cause mortality and cardiovascular mortality in hypertensive patients